Comparison of Early Versus Delayed Laparoscopic Cholecystectomy in Patients with Acute Calculus Cholecystitis: A Single-Centre Cross-Sectional Study (Journal of Rangpur Medical College, 2025)
Introduction: Acute calculus cholecystitis is a frequent cause of biliary morbidity, and laparoscopic cholecystectomy is the preferred treatment. Early surgery may limit inflammation and reduce pain duration, while delayed surgery allows resolution of acute symptoms. Comparing outcomes of early versus delayed intervention is essential to guide optimal surgical timing and improve patient recovery. Objective: To compare the outcomes of early versus delayed laparoscopic cholecystectomy in patients with acute calculus cholecystitis. Methods: Acomparative cross-sectional study was conducted at the Department of Surgery, Sylhet Women’s Medical College Hospital from January 2023 to December 2024. A total of 86 patients were divided into two groups: early surgery (within 72 hours of symptom onset) and delayed surgery (after 72 hours, following 4-6 weeks of conservative management). Outcomes assessed included duration of surgery, complications, conversion to open surgery, hospital stay, post-operative pain, time to return to normal activities, and port site infection. Results: Early surgery was associated with shorter duration of abdominal pain (3.05 vs. 4.15 days, p